Assembleias de peixes como parâmetro para avaliação de impactos ambientais na bacia do Rio Gramame- Paraíba e sua importância para as comunidades ribeirinhas - Turnell, Mariana Vieira (2012)
Due to anthropogenic activities, aquatic ecosystems are being rapidly modified in the entire world. The negative impact of pollutants, changes in the hydrology of the basin and changes in habitat, or introduction of exotic species, among others, result in the loss of water quality and difficulty in maintaining the integrity of these ecosystems. These changes, significantly affect the fish populations, causing a reduction in availability or even the disappearance of species that are not tolerant to the new environmental conditions. Consequently, fishermen who depend on resources from the aquatic environment can no longer subsist on fishing, which contributes to the loss of empiric knowledge and also in quality of life. The Gramame River, located in the state of Paraiba, Brazil, drains suburban areas of the region of João Pessoa, including its industrial district. As a result it receives a large amount of pollutants, particularly over the past 20 years, in addition to domestic sewage and agricultural pesticides, compounded by the introduction of exotic species. Upstream, near the industrial district, the river is surrounded by areas of sugar cane plantation, without riparian vegetation in most of its course. Coastal communities, residents in the water basin for decades, accompanied the whole process of degradation of the river water quality, now restricted in use by these communities. In this perspective, this study aimed to: (a) analyze the composition of the ichthyofauna in lotic and lentic environments along the basin of the Gramame River, comparing it with previous data in order to identify possible changes over time, (b) analyze the environmental perception from two riverine communities (Gramame and Mituaçu), their perceived changes in the river and fishing due to anthropogenic actions, and (c) relate the distribution of fish with the water quality (phosphorous and nitrogen nutrients). To obtain the data in the communities, a combination of qualitative and quantitative methods was used. The qualitative methods consisted of semi-structured interviews, snowball method and participant observation. The data were analyzed based on the model of unifying the various individual competences. On the other hand, quantitative data were statistically analyzed. Thirty eight fishermen were interviewed in both communities, of both genders, aged between 24 and 75 years. The ichthyofauna was collected with several fishing gear (fishing nets, fish traps, gererê and covos), always taking into account the physiographic and physiognomic peculiarities of each of the sampling points. The data for fish species were submitted to statistical analysis in order to ascertain whether there were significant differences in these parameters between sampling points. Regarding the limnological study, the sampling period were both in winter and summer, and the locations of water collection corresponded to the same sites where fish species where collected. The survey results show significant changes in fish fauna, especially with regard to the emergence of exotic species, which are now dominant in certain parts of the basin, with potential impacts to native fish fauna. It was also found that the fishermen noticed the differences in ichthyofauna and in the river. Despite the observed impacts, this environment is still important economically and socially, to promote the livelihood of many families. From the results obtained in this work it is concluded that there is urgency in formulating strategies for the sustainable use of this basin, integrating social, economic and environmental, in order to promote, among other benefits, the survival of fishing communities that depend on this the ecosystem.